Polymer Film Dewetting by Water/Surfactant/Good‐Solvent Mixtures: A Mechanistic Insight and Its Implications for the Conservation of Cultural Heritage. Issue 25 (11th January 2018) - Baglioni, Michele; Montis, Costanza; Chelazzi, David; Giorgi, Rodorico; Berti, Debora; Baglioni, Piero
Abstract: Aqueous nanostructured fluids (NSFs) have been proposed to remove polymer coatings from the surface of works of art; this process usually involves film dewetting. The NSF cleaning mechanism was studied using several techniques that were employed to obtain mechanistic insight on the interaction of a methacrylic/acrylic copolymer (Paraloid B72) film laid on glass surfaces and several NSFs, based on two solvents and two surfactants. The experimental results provide a detailed picture of the dewetting process. The gyration radius and the reduction of the T g of Paraloid B72 fully swollen in the two solvents is larger for propylene carbonate than for methyl ethyl ketone, suggesting higher mobility of polymer chains for the former, while a nonionic alcohol ethoxylate surfactant was more effective than sodium dodecylsulfate in favoring the dewetting process. FTIR 2D imaging showed that the dewetting patterns observed on model samples are also present on polymer‐coated mortar tiles when exposed to NSFs. Abstract : Aqueous nanostructured fluids (NSFs) are established tools with unique efficacy in the removal of hydrophobic polymer coatings from works of art. Here, we investigated the interaction of p(EMA/MA) films and NSFs to disentangle the mechanism of NSFs‐induced polymer film dewetting. Experimental data on simplified polymer‐coated coverglasses highlighted the specific role of each NSF component in kinetically promoting polymer dewetting. FTIR imaging on polymer‐coated mortar tiles confirmed the reliability of the theoretical description of NSFs‐polymer interaction in real case studies.